Applying Indigenous Knowledge to Innovations in Social Work Education. (March 2017) - Hertel, Amy Locklear
Grounded in an indigenous holistic worldview and borrowing from the four Rs (values of relationships, responsibility, reciprocity, and redistribution), this article supports the inclusion of translational science and the integration of core metacompetencies into social work doctoral education as innovations in the field of social work science. The author argues that these innovations will enhance the ability of social–work–trained researchers to serve on transdisciplinary research teams, which are necessary to address complex metaproblems found in the natural world. Further, the author asserts that transdisciplinary scientific integration is helpful to social work science, as it builds awareness and appreciation of social work scholarly inquiry, promotes the inclusion of social work values in scientific research, and helps erode the scientific hierarchy that has traditionally existed between the natural and social sciences. By leveraging personal experiences in transdisciplinary education, the author offers a conceptual framework for innovations in doctoral education.